Manipulation Of Expressive Symbol At Hindus Religious Practices In Mataram City - I Wayan Ardhi Wirawan (Jayapangus Press, 2020)
This study aims to conduct a study of the manipulation of expressive symbol at Hindus religious practices in Mataram city, West Nusa Tenggara. The design of this research is interpretive descriptive by focusing on case studies the mechanism of manipulation expressive symbols at Hindu community. Based on the results of the study found that the mechanism of manipulation expressive symbol begins with cultural adaptation and reinterpretation of a number symbols used as a medium to realize the Vedic teachings. The mechanism of manipulation expressive symbol in this research systematic flow through at four domains, namely cultural adaptation of Hindus religious practices in the realm of expressive symbols, the synergization of expressive symbols in responding the development of science and technology, the representation of expressive symbol contestation in the dynamics of Hindu civilization, as well as the reproduction and reproduction of expressive symbols in Hindus religious practice.